2021
DOI: 10.1039/d0tc05691j
|View full text |Cite
|
Sign up to set email alerts
|

Ternary organic solar cells with 16.88% efficiency enabled by a twisted perylene diimide derivative to enhance the open-circuit voltage

Abstract: For the high-efficiency PM6:Y6 binary system, there is still space for narrowing the lowest unoccupied molecular orbital (LUMO) level offset (0.36 eV) between PM6 and Y6 to further mitigate energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…It also indicates a better crystalline/mixing domain interface is formed to yield high carrier generation. The mobilities extracted by the space‐charge‐limited‐current (SCLC) method [ 8 ] are shown in Figure 1f. For T‐Mono‐FAs films, balanced and high carrier transport is achieved (T‐C 61 DMI: μ h (hole mobility) / µ e (electron mobility) = 1.25; T‐PC 61 BM: μ h / µ e = 1.28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also indicates a better crystalline/mixing domain interface is formed to yield high carrier generation. The mobilities extracted by the space‐charge‐limited‐current (SCLC) method [ 8 ] are shown in Figure 1f. For T‐Mono‐FAs films, balanced and high carrier transport is achieved (T‐C 61 DMI: μ h (hole mobility) / µ e (electron mobility) = 1.25; T‐PC 61 BM: μ h / µ e = 1.28).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b shows the hole‐transfer dynamics by the biexponential fit of the ≈590 nm bleach signal. The fast components ( τ 1 ) represent the ultrafast exciton dissociation in the mixing region, [ 8c,11 ] which are ≈0.32, ≈0.25, ≈0.27, ≈0.35, and ≈0.36 ps, for PM6:Y6, T‐CDMI, T‐PCBM, T‐Bis‐PCBM, T‐ICBA. This result corresponds well with the intermolecular distances in the mixing region.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the target application, the proclivity for PDI to π‐π stack and form large aggregates in the solid‐state may need to be circumvented to enable high performance [22,23] . Thus, to prevent PDI over‐aggregation in the solid‐state, it is possible to synthetically introduce a spacer core in between two or more PDI units [24–41] . These multicomponent PDI materials are highly regarded not only for their capacity to inhibit over‐aggregation, but also enable balanced charge dissociation and isotropic charge transport [23] …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most of the highly efficient ternary OSCs have been achieved via the significant improvement of J sc and V oc , attributed to the complementary absorption to expand the coverage of solar spectrum and the matched interfacial contact with suppressed charge recombination loss at ternary heterojunction. [ 19–21 ] However, their FF values are generally below 78%, [ 13,22–25 ] which is much smaller than silicon and perovskite cells. [ 26 ] Recent works have demonstrated that there is much room to promote the device efficiency by improving FF.…”
Section: Introductionmentioning
confidence: 99%